2017
DOI: 10.1097/mca.0000000000000520
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fasting blood glucose variability and coronary artery collateral formation in type 2 diabetes patients with coronary artery disease

Abstract: Glycemic variability is not associated with coronary collateral artery formation in patients with type 2 diabetes mellitus and CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The results of this study also showed that the proportion of diabetic patients with poor CCC was higher than that of patients with good CCC, suggesting that diabetes is related to poor CCC establishment and opening. Elevated blood glucose level and insulin resistance can lead to endothelial cell dysfunction, resulting in reduced NO and pro-angiogenic factor secretion and the inhibition of pro-angiogenic factor activity ( 35 , 36 ). Blood glucose control and reduced insulin resistance in diabetic patients may avoid reduced collateral circulation in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also showed that the proportion of diabetic patients with poor CCC was higher than that of patients with good CCC, suggesting that diabetes is related to poor CCC establishment and opening. Elevated blood glucose level and insulin resistance can lead to endothelial cell dysfunction, resulting in reduced NO and pro-angiogenic factor secretion and the inhibition of pro-angiogenic factor activity ( 35 , 36 ). Blood glucose control and reduced insulin resistance in diabetic patients may avoid reduced collateral circulation in these patients.…”
Section: Discussionmentioning
confidence: 99%